JARAK FUNGSI KE RUANG FUNGSI BAIRE KELAS SATU - , I MADE ARI SUSENA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The distance of a point x to a set A in a metric space is defined by the supre-mum of the distances of x to each point in the set A. In this thesis, we will discuss about the distance of a function f : X E to Bl(X, E), where Bl(X, E) denotes the space of Baire one functions from a metric space X to a Banach space E. In order to find the distance estimation, we will use two concepts, that are concept of index fragmentability and concept of oscillation function. As a consequence of the estimation result by using oscillation concept is for every separately continuous function f :X xK IR where X is a completely metrizable topological space and K is a compact topological space, there is a G6-dense set D C X such that f continuous on D x K.